Turbulent transport and reactions of plant-emitted hydrocarbons in an Amazonian rain forest. (15th June 2022) - Fuentes, Jose D.; Gerken, Tobias; Chamecki, Marcelo; Stoy, Paul; Freire, Livia; Ruiz-Plancarte, Jesus
Abstract: The processes governing the temporal and spatial patterns of isoprene and monoterpenes emitted by a rainforest in the central Amazon region of Brazil is investigated using a combination of field experiments and numerical simulations. Specifically, Large Eddy Simulations (LES) were used to resolve emissions of isoprene and monoterpenes, turbulent transport, and air chemistry. The coupled chemistry-transport LES included the effects of isoprene and monoterpenes reactivity due to reactions with hydroxyl radical and ozone. The LES results are used to compute vertically resolved budgets of isoprene and monoterpenes in the rainforest canopy in response to emissions, turbulent transport, surface deposition, and air chemistry. Results indicated that emission and dispersion dominated the isoprene budget as the gases were transported out of the canopy space. In a region limited by nitrogen oxides (with prevailing nitric oxide levels of < 0.5 parts per billion), the in-canopy chemical destruction removed approximately 10% of locally emitted monoterpenes. Hydroxyl radical production rates from the ozonolysis of monoterpenes amounted to ≈ 2 × 1 0 6 r a d i c a l s cm − 3 s − 1 and had similar magnitude to the light-dependent hydroxyl radical formation. One key conclusion was that the Amazonia rainforest abundantly emitted monoterpenes whose in-canopy ozonolysis yielded hydroxyl radicals in amounts similar to the magnitude of light-dependent formation. Reactions of monoterpenes and isoprene with hydroxyl radical and ozone were necessary for the maintenance of the Amazon rainforest canopy as a photochemically active environment suitable to generate oxidants and secondary organic aerosols. Highlights: Ozonolysis of rainforest emitted monoterpenes yielded hydroxyl radicals in amounts similar to the magnitude of light-dependent formation. Ozonelysis of monoterpenes produced concentrations of hydroxyl radicals similar the amounts consumed by the reaction with isoprene. Monoterpenes and isoprene reactions with hydroxyl radical and ozone maintained an environment suitable to generate oxidants.